Pemetaan Suara dan Perolehan Kursi Partai Politik di Kota Balikpapan dalam Pemilihan Umum Legislatif Tahun 2019 - Risendy Agastya; Mohammad Taufik; Melati Dama (Jurnal Ilmu Pemerintahan, 2024)
This study aims to describe how the political map acquires and converts the votes of political parties in Balikpapan City in the 2019 Legislative Election. Based on the results of the study using descriptive analysis research and using a literature study research approach and the concept used is thematic map concept which contains information on certain (specific) themes and is used for certain interests, one of which is politics. Then to find out the seat conversion using the divisor sainte lague method. The results of the study show that the map of the spread of the vote acquisition for legislative candidates in 6 electoral districts shows that Abdulloh, who comes from the Golongan Karya Party, has the most votes with 6,285 votes, then in political party votes, the PDIP Party becomes the party with the most votes, namely 30 sub-districts out of 34 sub-districts as a whole. In the combined vote acquisition between political parties and legislative candidates, the Golongan Karya Party became the party with the most votes, namely 13 sub-districts which were also in the conversion of seats, the Golongan Karya Party also won the most seats with 11 seats.